KOMITMEN ORGANISASI DAN KEPUASAN KERJA MENYEBABKAN TINDAKAN CYBERLOAFING - Okka Adittio Putra; Dwinda Agustintia; Syafri Yanto (JURNAL ILMIAH EDUNOMIKA, 2024)
Abstract This research aims to determine the relationship between organizational commitment and job satisfaction with cyberloafing in the Rejang Lebong Regency State Civil Apparatus generation and an employee is not happy with the work they do, job satisfaction is an employee's emotional response to a work situation which is determined by achieving results, meeting or exceeding expectations. Cyberloafing is the behavior of using the internet for personal gain during working hours for purposes that are not related to work activities. The sampling technique used was random sampling technique via Googleform. The measuring instrument used in this research is a Likert scale where the variables Organizational Commitment and job satisfaction are 15 item statements and Cyberloafing is 19 item statements. The results of data analysis using the regression test showed that the commitment correlation coefficient was -.518 and p = 0.026 (p < 0.05) while satisfaction was -.822 and p = 0.016 (p < 0.05). These results indicate that there is a significant negative relationship between organizational commitment and job satisfaction with cyberloafing. The higher organizational commitment and job satisfaction, the lower cyberloafing. Keyword: commitment organizational, job satisfactions, cyberloafing, State Civil Apparatus